Characteristics of constant and intermittent mechanical low back pain. (2nd April 2016) - McIntosh, Greg; Carter, Tom; Hall, Hamilton
Abstract: The objective was to compare characteristics of patients with mechanical constant versus intermittent low back pain (LBP) as they progressed through non-operative treatment. A single-page clinician-administered questionnaire was utilised in a consecutive sample of 62 LBP patients during their initial assessment, then readministered weekly until treatment was concluded or pain abolished. At initial assessment, 45% had constant pain ( n  = 28), 55% had intermittent pain ( n  = 34). For those who had intermittent pain at assessment, no one regressed to constant pain by the conclusion of treatment. For those presenting with constant pain, 18% remained constant while 82% improved; 43% progressed to intermittent pain and 39% achieved pain abolition. For the 42 respondents who specified a reason for their change in pain presence, 76% stated that their pain decrease was due to a positive response to exercise, while 17% blamed exercising for a flare-up. Only 7% said that the change was related to a difference in medication. In the constant pain group, 87% had a positive response to exercise, 4% blamed exercising for a flare-up and 9% believed the alteration was due to a change in medication. Back pain usually runs a protracted relapsing course. This study provides data on characteristics and progression of constant and intermittent back pain throughout a course of non-operative treatment.